2012
DOI: 10.1016/j.ejps.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Semi-physiologically based pharmacokinetic modeling of paclitaxel metabolism and in silico-based study of the dynamic sensitivities in pathway kinetics

Abstract: Purpose: To build a semi-physiologically based pharmacokinetic model describing the uptake, metabolism and efflux of paclitaxel and its metabolites and investigate the effect of hypothetical genetic polymorphisms causing reduced uptake, metabolism or efflux in the pathway by model simulation and sensitivity analysis. Methods: A previously described intracellular pharmacokinetic model was used as a starting point for model development. Kinetics for metabolism, transport, binding and systemic and output compartm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…On the contrary, there was no significant association observed between the ABCB1 G2677T/A polymorphism and hematologic or nonhematologic paclitaxel toxicity in metastatic breast cancer patients [44]. A study by Fransson and coworkers revealed that SNPs causing changes in metabolism or transport had a minimal effect on the plasma concentration of paclitaxel; however, its main metabolite (6a-hydroxypaclitaxel) may be affected by even small changes in the capacity of transport or metabolism [45]. This study proposes that genetic polymorphisms may play an important role for individualizing paclitaxel treatment [45].…”
Section: Abcb1mentioning
confidence: 99%
“…On the contrary, there was no significant association observed between the ABCB1 G2677T/A polymorphism and hematologic or nonhematologic paclitaxel toxicity in metastatic breast cancer patients [44]. A study by Fransson and coworkers revealed that SNPs causing changes in metabolism or transport had a minimal effect on the plasma concentration of paclitaxel; however, its main metabolite (6a-hydroxypaclitaxel) may be affected by even small changes in the capacity of transport or metabolism [45]. This study proposes that genetic polymorphisms may play an important role for individualizing paclitaxel treatment [45].…”
Section: Abcb1mentioning
confidence: 99%
“…Lal et al 10 found that the clearance rate of paclitaxel in CC-GG-CC wild-type patients with C1236T, G2677T/ A, and C3435T mutations was significantly increased compared with CT-GT-CT and TT-TT-TT mutants, while the plasma peak drug concentration was significantly decreased. Conversely, Fransson et al 11 reported that SNPs have only a small influence on the plasma concentration of paclitaxel, but that even a slight change of transfer or metabolism would affect the concentration of the main metabolic products of paclitaxel. The effect of ABCB1 on drug toxicity is therefore of greater importance than the pharmacokinetics of the drug itself.…”
Section: Introductionmentioning
confidence: 98%